Livros e leituras em Vera Cartonera: produção, circulação e apropriação de bens culturais - Santomero, Lucila (Universidad Nacional del Litoral, 2022)
The purpose of the article is to present the project of the university publishing house Vera Cartonera and to reflect on the interventions proposed in the field of public communication of science and literature as a university extension policy. For this, two planes are taken up: on the one hand, the actions that Vera proposes in relation to the production, circulation and social appropriation of knowledge through the “cardboard book"” and; on the other hand, in the field of publications on university extension, that is, the production of academic texts and narratives that seek to return to the extension experiences carried out and with which the project dialogues. The main objective is to problematize the practices themselves, review decisions and thus enhance future actions. In this direction, the work aims to make visible the power of university extension when it is linked to teaching and research practices.